2022
DOI: 10.2147/idr.s364439
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF MS-Based Clustering and Antifungal Susceptibility Tests of Talaromyces marneffei Isolates from Fujian and Guangxi (China)

Abstract: Introduction Talaromyces marneffei is a life-threatening pathogen that causes systemic talaromycosis in immunocompromised and acquired immunodeficiency syndrome (AIDS) patients. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) as a tool to cluster T. marneffei isolates is rarely reported and the data on antifungal susceptibility of T. marneffei isolated in the southern region of China, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
5
2
0
Order By: Relevance
“…The overall finding of echinocandin in this study was comparatively high compared with other antifungals when tested against both forms of T. marneffei. This phenomenon is consistent with the finding of Fang et al 33…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The overall finding of echinocandin in this study was comparatively high compared with other antifungals when tested against both forms of T. marneffei. This phenomenon is consistent with the finding of Fang et al 33…”
Section: Discussionsupporting
confidence: 94%
“…The overall finding of echinocandin in this study was comparatively high compared with other antifungals when tested against both forms of T. marneffei . This phenomenon is consistent with the finding of Fang et al 33 and Lei et al 34 The present findings supported the claim that echinocandins might have little to no effect on T. marneffei yeast as proposed by Fang et al 33 …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In 2018, Lei et al [78] observed that the YeastOne TM YO10 assay may be a viable option for susceptibility testing, particularly for the susceptibility profile of echinocandins, azoles, and amphotericin B against the yeast phase of T. marneffei. A recent publication by Fang et al [79] confirmed the observations of Lei et al [78], which observed that the yeast forms of the T. marneffei isolates are inhibited by amphotericin B and azoles (itraconazole and voriconazole with MIC 50 and MIC 90 ≤ 0.015 µg/mL). Furthermore, Fang et al [79] have shown the antifungal activity of triazoles to be superior to echinocandins and 5-fluorocytosine for the yeast phase of T. marneffei.…”
Section: Challenges and Perspectives For The Diagnosis Of Talaromycosissupporting
confidence: 61%
“…A recent publication by Fang et al [79] confirmed the observations of Lei et al [78], which observed that the yeast forms of the T. marneffei isolates are inhibited by amphotericin B and azoles (itraconazole and voriconazole with MIC 50 and MIC 90 ≤ 0.015 µg/mL). Furthermore, Fang et al [79] have shown the antifungal activity of triazoles to be superior to echinocandins and 5-fluorocytosine for the yeast phase of T. marneffei. This information may be useful to determine the presence of T. marneffei, and the evolution of the strains in terms of resistance to antifungal drugs.…”
Section: Challenges and Perspectives For The Diagnosis Of Talaromycosissupporting
confidence: 61%